Cloud Computing: Principles, Systems and Applications - Antonopoulos, Nick; Gillam, Lee (Computer Communications and Networks, 2010)
Cloud computing continues to emerge as a subject of substantial industrial and academic interest. Although the meaning and scope of "cloud computing" continues to be debated, the current notion of clouds blurs the distinctions between grid services, web services, and data centers, among other areas. Clouds also bring considerations of lowering the cost for relatively bursty applications to the fore. Cloud Computing: Principles, Systems and Applications is an essential reference/guide that provides thorough and timely examination of the services, interfaces and types of applications that can be executed on cloud-based systems. The book identifies and highlights state-of-the-art techniques and methods for designing cloud systems, presents mechanisms and schemes for linking clouds to economic activities, and offers balanced coverage of all related technologies that collectively contribute towards the realization of cloud computing. With an emphasis on the conceptual and systemic links between cloud computing and other distributed computing approaches, this text also addresses the practical importance of efficiency, scalability, robustness and security as the four cornerstones of quality of service. Topics and features: explores the relationship of cloud computing to other distributed computing paradigms, namely peer-to-peer, grids, high performance computing and web services, presents the principles, techniques, protocols and algorithms that can be adapted from other distributed computing paradigms to the development of successful clouds, includes a Foreword by Professor Mark Baker of the University of Reading, UK, examines current cloud-practical applications and highlights early deployment experiences, elaborates the economic schemes needed for clouds to become viable business models. This book will serve as a comprehensive reference for researchers and students engaged in cloud computing. Professional system architects, technical managers, and IT consultants will also find this unique text a practical guide to the application and delivery of commercial cloud services. Prof. Nick Antonopoulos is Head of the School of Computing, University of Derby, UK. Dr. Lee Gillam is a Lecturer in the Department of Computing at the University of Surrey, UK. TOC:Part I: Cloud Base,- Tools and Technologies for Building Clouds.- A Taxonomy, Survey and Issues of Cloud Computing Ecosystems.- Towards a Taxonomy for Cloud Computing from an e-Science Perspective.- Examining Cloud Computing from the Perspective of Grid and Computer-Supported Cooperative Work.- Overview of Cloud Standards.- Part II: Cloud Seeding.- Open and Interoperable Clouds: the Cloud@HomeWay.- A Peer-to-Peer Framework for Supporting MapReduce Applications in Dynamic Cloud Environments.- Enhanced Network Support for Scalable Computing Clouds.- YML-PC: A Reference Architecture Based on Workflow for Building.- Scientific Private Clouds.- An Efficient Framework for Running Applications on Clusters, Grids and Clouds.- Resource Management for Hybrid Grid and Cloud Computing.- Peer-to-Peer Cloud Provisioning: Service Discovery and Load-Balancing.- Mixing Grids and Clouds: High-throughput Science using the Nimrod Tool Family.- Part III: Cloud Breaks.- Cloud Compliance: A Framework for Using Cloud Computing in a Regulated World.- Cloud Computing: Data Confidentiality and Interoperability Challenges.- Security Issues to Cloud Computing.- Securing the Cloud.- Part IV: Cloud Feedback.- Technologies for Enforcement and Distribution of Policy in Cloud Architectures.- The PRISM On-demand Digital Media Cloud.- Cloud Economics: Principles, Costs and Benefits.- Towards Application-Specific Service Level Agreements: Experiments in Clouds and Grids.